2017
DOI: 10.1111/cpr.12371
|View full text |Cite
|
Sign up to set email alerts
|

Impact of miR‐26b on cardiomyocyte differentiation in P19 cells through regulating canonical/non‐canonical Wnt signalling

Abstract: Our results indicated that miR-26b exerts a role on promoting cardiomyocyte differentiation of P19 cells by controlling the canonical and non-canonical Wnt signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…This mode of pairing usually negatively regulates the translation of the target through the repression of the initial ribosome binding to the mRNA or the ribosome drop-off [ 21 ]. The analysis of miRNA expression in cardiomyocyte progenitor cells (CMPCs) showed that 188 miRNAs were detectable in proliferating CMPCs and 195 in differentiated CMPCs such as miR1, miR1-2, miR499, miR322, miR503, miR208, miR133, and miR26b [ 30 , 31 , 32 , 33 , 34 ]. MiR-208, together with miR-1, miR-133, and miR-206, are called myomiRs as they are expressed specifically in the heart and skeletal muscles.…”
Section: Regulatory Pathways and Epigenetic Control Of Cardiomyogementioning
confidence: 99%
“…This mode of pairing usually negatively regulates the translation of the target through the repression of the initial ribosome binding to the mRNA or the ribosome drop-off [ 21 ]. The analysis of miRNA expression in cardiomyocyte progenitor cells (CMPCs) showed that 188 miRNAs were detectable in proliferating CMPCs and 195 in differentiated CMPCs such as miR1, miR1-2, miR499, miR322, miR503, miR208, miR133, and miR26b [ 30 , 31 , 32 , 33 , 34 ]. MiR-208, together with miR-1, miR-133, and miR-206, are called myomiRs as they are expressed specifically in the heart and skeletal muscles.…”
Section: Regulatory Pathways and Epigenetic Control Of Cardiomyogementioning
confidence: 99%
“…Cells were cultured in α-minimal essential medium with 10% fetal bovine serum (both from Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA), 100 U/ml penicillin and 100 µg/ml streptomycin (Hyclone; GE Healthcare Life Sciences, Logan, UT, USA) at 37˚C in an incubator containing 5% CO 2 . To induce P19 cell differentiation, DMSO (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) was added to the culture medium at a final concentration of 1.0% (27)(28)(29). P19 cells aggregated over the following 4 days to form embryoid bodies (EBs), during which time the medium was replenished every 24 h. On day 4, the EBs were transferred into a 6-well plate and cultured in DMSO-free medium to allow adherent proliferation of P19 cells.…”
Section: Methodsmentioning
confidence: 99%
“…21 The rest of the information related to the assay is described in Supplemental Experimental Procedures and in the Table S2. 21 The rest of the information related to the assay is described in Supplemental Experimental Procedures and in the Table S2.…”
Section: Immunostainingmentioning
confidence: 99%
“…The major experimental steps are described in accordance with the previous description. 21 The rest of the information related to the assay is described in Supplemental Experimental Procedures and in the…”
Section: Immunostainingmentioning
confidence: 99%